SPI Memoderasi Pengaruh SIA, Tekanan Keuangan, Komitmen Organisasi dan Budaya Organisasi Pada Kecenderungan Kecurangan - Dewi, Risma; Suardana, Ketut Alit (E-Jurnal Akuntansi, 2022)
This study aims to determine the effect of accounting information systems, financial pressure, organizational commitment and organizational culture on fraud tendencies in Bangli Regency with the internal control system as a moderating variable. The research population is 34 Bangli Regency Regional Apparatus Organizations. Sampling using purposive sampling method and get as many as 60 respondents as research samples. Research data obtained from distributing questionnaires. Data analysis using moderation linear regression method. The results showed that accounting information systems and organizational culture had a significant negative effect on fraud tendencies, organizational commitment had a significant positive effect on fraud tendencies, but financial pressure and internal control systems had no significant effect. The results of the moderation analysis show that the internal control system is able to moderate the influence of accounting information systems, organizational commitment and organizational culture on fraud tendencies. The internal control system is unable to moderate the effect of financial pressure on fraud tendencies. Keywords: Fraud Tendency; Government institution; Fraud Triangle; Internal Control System.